2021
DOI: 10.1029/2021gl094773
|View full text |Cite
|
Sign up to set email alerts
|

Strong Diurnal Pulsing of Cold Clouds in Rapidly Intensifying Tropical Cyclones

Abstract: The radially outward propagating diurnal signal in the upper-level clouds (diurnal pulse) is a prominent cyclical feature of tropical cyclones (TCs). This study examines relationships between diurnal pulses and TC intensity changes using satellite Infrared data from 2001 to 2018. The occurrence and duration of diurnal pulses 24 hr prior to or during TC intensity change are strongly correlated with TC intensification rate. Rapidly intensifying (RI) TCs have a markedly higher frequency (60%-80%) of very long-dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…Precipitation pulse is objectively identified using an algorithm similar as the identification of cold‐cloud diurnal pulse (Ditchek, Molinari, et al., 2019; Ditchek, Corbosiero, et al., 2019; Zhang & Xu, 2021b). First, the 600 × 600 km storm‐centered rain rate 6‐hr difference fields (current minus previous 6 hr) are extracted from the IMERG precipitation data.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Precipitation pulse is objectively identified using an algorithm similar as the identification of cold‐cloud diurnal pulse (Ditchek, Molinari, et al., 2019; Ditchek, Corbosiero, et al., 2019; Zhang & Xu, 2021b). First, the 600 × 600 km storm‐centered rain rate 6‐hr difference fields (current minus previous 6 hr) are extracted from the IMERG precipitation data.…”
Section: Methodsmentioning
confidence: 99%
“…Taking super typhoon Vongfong (2014) as an example (Figure S2 in Supporting Information S1), the objective algorithm well detects the outward propagating feature of the TC precipitation pulses, either in a panel view or a time-radius cross section perspective. In parallel, cold-cloud pulse information is derived from the global TC cold-cloud pulse data set developed by Zhang and Xu (2021b). Overall, 2,841 precipitation pulse and 3,524 cold-cloud pulse events are identified out of the 5,517 TC days from 2001 to 2018.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies suggested that TC intensification is strongly related to their upper-level clouds and stratiform precipitation (Tao et al, 2017;Fischer et al, 2018;Zhang and Xu, 2021). Recent theoretical and modeling studies have suggested that the crucial role of cloud-radiation feedback (CRF) in TC genesis and development (Bu et al, 2014;Fovell et al, 2016;Wing et al, 2016;Ruppert et al, 2020;Smith et al, 2020;Yang and Tan, 2020;Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%